2016
DOI: 10.1088/0957-4484/27/49/494005
|View full text |Cite
|
Sign up to set email alerts
|

AFM study shows prominent physical changes in elasticity and pericellular layer in human acute leukemic cells due to inadequate cell–cell communication

Abstract: Biomechanical properties of single cells in-vitro or ex-vivo and its pericellular interface have recently attracted a lot of attention as a potential biophysical (and possibly prognostic) marker of various diseases and cell abnormalities. At the same time, the influence of the cell environment on the biomechanical properties of cells is not well studied. Here we use atomic force microscopy (AFM) to demonstrate that cell-cell communication can have a profound effect on both cell elasticity and its pericellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 73 publications
(156 reference statements)
0
9
0
Order By: Relevance
“…For a qualitative description of the “amount” of glycocalyx on the endothelium, the following product of brush length and grafting density can be used 50 : …”
Section: Analysis and Classification Of Indentation Curvesmentioning
confidence: 99%
“…For a qualitative description of the “amount” of glycocalyx on the endothelium, the following product of brush length and grafting density can be used 50 : …”
Section: Analysis and Classification Of Indentation Curvesmentioning
confidence: 99%
“…For example, the tumor microenvironment is composed of blood and lymphatic vessels and a variety of nonmalignant host cells, including fibroblasts, monocytes, macrophages, mast cells, mesenchymal stem cells and so on [89], [90]. Recent studies have shown that cell-cell contacts have a significant effect on cell mechanics [91]- [93]. In 2014, Guo et al [91] applied AFM to investigate the mechanical properties of cells in three different microenvironments as related to cell-cell contacts, including isolated cells, cells residing on the periphery of a contiguous cell monolayer, and cells on the inside of a contiguous cell monolayer.…”
Section: Cell-cell Contactmentioning
confidence: 99%
“…2C. In 2016, Guz et al [93] investigated the effects of cell-cell communication on the elasticity of human acute leukemic cells. The Young's modulus of cells grown in low density (5000 cells/ml) and high density (2 × 10 5 cells/ml) was measured respectively, showing that the Young's modulus significantly decreased in high density than in low density.…”
Section: Cell-cell Contactmentioning
confidence: 99%
“…Biomechanical properties of cancer cells have shown to be closely related with cancer pathology and metastasis state abnormalities 7, 8. It is also found that the biomechanical changes were correlated with the cell-cell communications 9 and microenvironment 10, 11. Understanding the biomechanical properties of tumor cells can not only help to elucidate the mechanisms behind disease progression, but also provide important information for cancer diagnosis and treatment 12, 13, 14.…”
Section: Introductionmentioning
confidence: 99%